Approaches to Experimental Pit House Reconstructions in the Japanese Central Highlands: Architectural History, Community Archaeology and Ethnology - John Ertl (EXARC, 2021)
In Japan, over 1,000 prehistoric house reconstructions have been built at 360 different locations since 1949. Pit houses from Neolithic Jomon Period (14,000–300BC) are the most common but they are mostly based on archaeological remains limited to pits and postholes. Therefore, decisions on material and structure come from various sources, some based on research and others rooted in cultural ideologies or individual’s preferences. This paper compares reconstructions at three sites in the Central Highlands region of Japan. Despite the similarities in archaeological remains, the approaches toward reconstructions at each site are remarkably different. At Togariishi site (built 1949) the pit house design was made by Horiguchi Sutemi, a modernist architect and historian inspired by the past to find a Japanese essence in traditional farmhouses and tea houses that could intermix with Western architecture. At Idojiri site (first built 1958) archaeologists rejected mainstream academic concerns and embraced a community-centered approach to archaeological research and reconstruction. Lastly, the four pit houses at Umenoki site (built from 2014) were based on ethnographic examples from North America and were built by a carpenter and re-enactor who collaborated with the site archaeologists and the public.